Explosive detection using a novel dielectric barrier discharge ionisation source for mass spectrometry. (25th January 2018) - Fletcher, Carl; Sleeman, Richard; Luke, John; Luke, Peter; Bradley, James W.
Abstract: The detection of explosives is of great importance, as is the need for sensitive, reliable techniques that require little or no sample preparation and short run times for high throughput analysis. In this work, a novel ionisation source is presented based on a dielectric barrier discharge (DBD). This not only affects desorption and ionisation but also forms an ionic wind, providing mass transportation of ions towards the mass spectrometer. Furthermore, the design incorporates 2 asymmetric alumina sheets, each containing 3 DBDs, so that a large surface area can be analysed. The DBD operates in ambient air, overcoming the limitation of other plasma‐based techniques which typically analyse smaller surface areas and require solvents or gases. A range of explosives across 4 different functional groups was analysed using the DBD with low limits of detection for cyclotrimethylene trinitramine (RDX) (100 pg), pentaerythritol trinitrate (PETN) (100 pg), hexamethylene triperoxide diamide (HMTD) (1 ng), and trinitrotoluene (TNT) (5 ng). Detection was achieved without any sample preparation or the addition of reagents to facilitate adduct formation.